Prevalence and costs of headaches for the public health system in a town in the interior of the state of São Paulo Prevalência e custos das cefaléias para o Sistema Público de Saúde de uma cidade do interior do Estado de São Paulo - Marcelo E. Bigal; Janaína O.M. Bigal; Carlos A. Bordini; José G. Speciali (Arquivos de Neuro-Psiquiatria)
Despite the high prevalence, impact and economic importance of headaches, studies on this subject are rare in Brazil. The aim of the present study was to estimate the prevalence of headaches in the public health system of a town in the interior of the State of São Paulo, as well as to estimate the costs resulting from its management. Data refer to the year of 1998 and were obtained according to the following steps: 1) territorial and demographic characterization of the municipality; 2) characterization of the financial indices and social well-being; 3) budget characteristics of the municipality; 4) evaluation of the structuring of the medical service; 5) determination of the prevalence of headaches at different patient care levels; and 6) calculation of the costs of headaches. Headaches represented 7.9% of all visits at basic health units, 9.7% in the emergency room and 1.1% of hospital admissions. The total costs were R$ 85,131.31 (US$ 70,942.76) corresponding to R$ 7.59 (US$ 6,32) per inhabitant/year. The present study shows the need for epidemiological and economic impact studies, which would provide the basis for the rational use of health funds. Apesar da grande prevalência, impacto e importância econômica das cefaléias, são incomuns os estudos referentes a esses aspectos em nosso meio. O presente estudo visa estimar a prevalência das cefaléias no sistema público de uma cidade do interior do Estado de São Paulo, bem como estimar os custos decorrentes de seu manejo. Os dados referem-se ao ano de 1998 e obedeceram às seguintes etapas: 1 -- caracterização territorial e demográfica do município; 2 -- caracterização de índices financeiros e de bem estar social; 3 -- características orçamentárias do município; 4 -- avaliação da estruturação do atendimento médico; 5 -- levantamento da prevalência das cefaléias nos diversos níveis de atendimento; 6 -- cálculo dos custos das cefaléias. Cefaléias foram responsáveis por 7,9% dos atendimentos em unidades básicas de saúde, 9,7% em pronto socorro e 1,1% das internações hospitalares. Os custos totais foram de R$ 85.131,31 (US$ 70,942.76) o que equivale a R$ 7,59 (US$ 6,32) por habitante/ano. Esse estudo demonstra a necessidade da realização de trabalhos epidemiológicos e de impacto econômico que permitam racionalizar o emprego de verbas para a saúde.